Enhancing acetate selectivity by coupling anodic oxidation to carbon monoxide electroreduction - Overa, Sean; Crandall, Bradie S; Shrimant, Bharat; Tian, Ding; Ko, Byung Hee; Shin, Haeun; Bae, Chulsung; Jiao, Feng (Nature catalysis, 2022)
Electrocatalytic conversion of carbon monoxide (CO) is being actively developed as a key component for tandem CO2 electrolysis. Great effort has been devoted to engineering CO reduction electrocatalysts for better multicarbon product selectivity. However, less work has focused on other performance parameters that are crucial for commercializing CO electrolysis, such as liquid product concentration and purity. Here, we present an internally coupled purification strategy to substantially improve the acetate concentration and purity in CO electrolysis. This strategy utilizes an alkaline-stable anion exchange membrane with high ethanol permeability and a selective ethanol partial oxidation anode to control the CO reduction product stream. We demonstrate stable 120-h continuous operation of the CO electrolyser at a current density of 200 mA cm−2 and a full-cell potential of <2.3 V, continuously producing a 1.9 M acetate product stream with a purity of 97.7%. The acetate stream was further improved to a concentration of 7.6 M at >99% purity by tuning the reaction conditions. Finally, a techno-economic analysis shows that a highly concentrated liquid product stream is essential to reduce the energy consumption of product separation.CO can be reduced electrocatalytically on Cu-based electrodes to acetate and ethanol; however, formation of mixed product streams creates a separation issue. Here, a selective anode for ethanol partial oxidation and an anion exchange membrane with high ethanol permeability are incorporated into an electrolyser to generate pure acetate (>99%) at high concentration (up to 7.6 M).